Case Report: Renal artery stenosis in children: ultrasound as a decisive diagnostic and therapy-accompanying technique! - Brasseler, Maire; Finkelberg, Ilja; Müntjes, Carsten; Cetiner, Metin (Frontiers in Pediatrics, 2023)
Introduction Renal artery stenosis in children is rare, and the recommended diagnostic algorithm, including techniques such as catheter-based angiography, CT angiography, magnetic resonance angiography, and ultrasound, is controversial in pediatric cohorts. Case presentation We report a case of an 11-year-old girl with renal artery stenosis in whom ultrasonography played a decisive role in confirming the diagnosis and accompanying therapeutic percutaneous transluminal renal artery angioplasty. Conclusion Improved ultrasound techniques and the examiner’s experience contribute to improving renal artery stenosis diagnosis in children. In particular, localized sensitive blood flow velocity analysis indicates the advantages of ultrasound compared to other imaging modalities in renal artery stenosis. Therefore, ultrasound should be a focus of future study designs addressing the search for the best diagnostic algorithm. Summary The advantages of ultrasound techniques in pediatric patients with renal artery stenosis compared to other imaging modalities are highlighted.